Physical activity and common tasks of California farm workers: California Heat Illness Prevention Study (CHIPS). - Mitchell, Diane C.; Armitage, Tracey L.; Bennett, Deborah H.; Schenker, Marc B.; Castro, Javier; Tancredi, Daniel J. (Journal of Occupational & Environmental Hygiene, 2018)
Farm workers are at risk of heat related illness (HRI), but their work rates that contribute to HRI have not been objectively assessed. The CHIPS study collected accelerometer data and characterized the physical activity of major farm tasks. Demographic information, work characteristics, and accelerometer data were collected from 575 farm workers in California. Each participating worker contributed measurements over one work shift. An Actical accelerometer was attached securely to a belt worn at the hip. Data were collected at one-minute intervals throughout the work shift. A total of 13 major work-task categories were defined. The mean physical activity counts per minute (cpm) and percentage of the shift spent at moderate and/or vigorous levels of activity were described for each task. Multiple linear regression models were constructed to determine the worker and environmental characteristics contributing to the physical activity level. Mean levels of physical activity ranged from 700 cpm (workers who carry produce) to a low of 150 cpm "ground pruners" who tend low-level plants, with an overall mean of 345 cpm or "light" activity (2 to ≤3 metabolic equivalents). The environmental temperature was the major factor associated with physical activity. A 10°C increase in the median temperature reduced the mean cpm by 135 (95% CI = 87, 193). Age and the tasks of sorting, ground pruning, and harvesting low-level crops were also negatively and independently associated with mean cpm. Incentivized (piece rate) pay, multi-task work, and irrigator work were positively associated with cpm. An interaction was found between piece rate and sex. Men's activity significantly increased (p < 0.001) by a mean of 95 cpm, (95% CI = 38.3, 150.7) if they were paid by the piece, but there was a non-significant association with women's activity level. Workers conducting multiple tasks, irrigators, men, and those earning incentivized (piece rate) pay had higher adjusted mean physical activity levels and are likely at increased risk of heat-related illness on hot days.